Influence of preparation time and pitch separation in switching of auditory attention between streams - Larson, Eric (Acoustical Society of America, 2013)
The ability to consciously switch attention between speakers of interest is necessary for communication in many environments, especially when multiple talkers speak simultaneously. Segregating sounds of interest from the background, which is necessary for selective attention, depends on stimulus acoustics such as differences in spectrotemporal properties of the target and masker. However, the relationship between top-down attention control and bottom-up stimulus segregation is not well understood. Here, two experiments were conducted to examine the time necessary for listeners to switch auditory attention, and how the ability to switch attention relates to the pitch separation cue available for bottom-up stream segregation.